2021
DOI: 10.3390/pathogens10040493
|View full text |Cite
|
Sign up to set email alerts
|

High Biofilm Formation of Non-Smooth Candida parapsilosis Correlates with Increased Incorporation of GPI-Modified Wall Adhesins

Abstract: : Candida parapsilosis is among the most frequent causes of candidiasis. Clinical isolates of this species show large variations in colony morphotype, ranging from round and smooth to a variety of non-smooth irregular colony shapes. A non-smooth appearance is related to increased formation of pseudohyphae, higher capacity to form biofilms on abiotic surfaces, and invading agar. Here, we present a comprehensive study of the cell wall proteome of C. parapsilosis reference strain CDC317 and seven clinical isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 52 publications
(81 reference statements)
3
16
0
Order By: Relevance
“…Compared to reference strain ATCC 2001, proteomic analysis of biofilm cells showed increased incorporation of adhesins in PEU1221, confirming the earlier noted correlation between biofilm-forming capacity and adhesin incorporation in Candida (Goḿez-Molero et al, 2015;Moreno-Martıńez et al, 2021). Not only the relative abundance of adhesin peptides was higher in strain PEU1221, also more different adhesin peptides and proteins were identified.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Compared to reference strain ATCC 2001, proteomic analysis of biofilm cells showed increased incorporation of adhesins in PEU1221, confirming the earlier noted correlation between biofilm-forming capacity and adhesin incorporation in Candida (Goḿez-Molero et al, 2015;Moreno-Martıńez et al, 2021). Not only the relative abundance of adhesin peptides was higher in strain PEU1221, also more different adhesin peptides and proteins were identified.…”
Section: Discussionsupporting
confidence: 84%
“…Previous work has shown that HBF phenotypes may coincide with increased cell surface hydrophobicity, increased cell-cell aggregation, and faster sedimentation in liquid (Goḿez-Molero et al, 2015;Moreno-Martıńez et al, 2021). This is also the case for PEU1221.…”
Section: Characterization Of Cluster III Adhesin Awp14mentioning
confidence: 70%
See 2 more Smart Citations
“…Previous studies have revealed correlations between the capacity to form biofilms and the incorporation of cell wall adhesins in Candida ( Gómez-Molero et al., 2015 ; Moreno-Martínez et al., 2021 ). This prompted us to investigate the incorporation of cell wall adhesins in strain PEU1221 in comparison to ATCC 2001, a low-biofilm-forming (LBF) strain, using a proteomic approach.…”
Section: Resultsmentioning
confidence: 99%